TOLERANSI JULANG SULAWESI (Rhyticeros cassidix) TERHADAP GANGGUAN HABITAT DI HUTAN PRODUKSI TERBATAS SUNGAI ANDAGILE - SUNGAI GAMBUTA - SUNGAI ILANGA BOLAANG MONGONDOW UTARA - Sudarmanto Angona; Martina A. Langi; Hard N. Pollo (Universitas Sam Ratulangi, 2022)
Abstract The research to measure the tolerance level of the Knobbed Hombil to the magnitude of habitat disturbance and the determinants of tree habitat used in the Limited Production Forest of Andagile River - Gambuta River - Ilanga River in North Bolaang Mongondow Regency. Based on the existing habitat disturbance, the Knobbed Hombil in the Andagile River Limited Production Forest - Gambuta River - Ilanga River, North Bolaang Mongondow has a tolerance level in habitats that have 5 to 3 remaining Forest Stratification and found in the Forest Stratification A (> 30 m), the Forest Stratification B (20 - 30 m), and Forest Stratification C (4 - 20 m). The place altitude above the sea level, the physiography, the slope, are suitable habitat conditions for the Knobbed Hombil and also along the trees that are used together with other animals; While it comes with a tolerated noise level by Knobbed Hombil. Key words: Knobbed Hombil Tolerance (Rhyticeros cassidix), Habitat disturbance, Limited Production Forest, North Bolaang Mongondow